Oxytocin and postpartum depression - a possible treatment for depressed mothers - Milena Leziak; Sylwiusz Niedobylski; Klaudia Żak; Michał Piwoński; Danuta Krasowska; Katarzyna Skórzyńska-Dziduszko (Kazimierz Wielki University, 2020)
Introduction and purpose: Postpartum depression (PPD) is one of the most common conditions in childbearing. It is estimated that 10-15% of mothers develop PPD. Oxytocin has recently been implicated in the pathophysiology of several neuropsychiatric disorders including PPD. The aim of this study is to, on the base of recent studies, investigate whether oxytocin has an impact on PPD and if it can be used as a way of diagnostic indicator or treatment. Brief description of the state of knowledgement: Studies indicate that there is a relationship between oxytocin and PPD. Depression and anxiety after delivery were observed more frequently among women with lower oxytocin plasma levels. Basing on the oxytocin plasma levels in the third semester of pregnancy, the risk of PPD can be predicted. This relationship was observed in women who were breastfeeding as well as in those who cessed. Some studies indicate that depression development may be inhibited thanks to oxytocin. Exogenous oxytocin has been proven to improve prosocial behaviour and reduce negative emotional responses in mother-children relations. It may also increase mother's attention to baby. Some studies have stated that intrapartum oxytocin administration decreases the rate of PPD symptoms but studies on treatment with oxytocin are not unanimous. Conclusions: Oxytocin plays an undeniable role in pathophysiology of postpartum depression and it may be regarded as a diagnostic indicator and therapeutic target. However, more studies are needed to clarify this intricate relationship.